A statistical analysis of inter-state disparities in agricultural development across India - MAHAL, AMRIT KAUR; SINGH, PRITPAL; KUMAR, SUNNY; KAUR, SIMRANJIT (The Indian Journal of Agricultural Sciences, 2026)
A comparative analysis of inter-state variations for three years i.e. 2019–20 to 2021–22 in agricultural development across India had been done by using secondary data from the major agricultural states for 28 key development indicators related to agriculture for Triennium Ending (TE) 2022. The composite indices of development based on the optimum combination of indicators related to agriculture had been worked out for four zones and the overall agricultural states of India. The results of Composite Index (CI) showed that Punjab (0.32), West Bengal (0.37), Gujarat (0.52), and Kerala (0.58) ranked highest in the north, east, west, and south zones, respectively. Overall, the state-wise CI ranged from 0.47 in Punjab to 0.83 in Odisha. The states were further ranked and categorised into high (H), high middle (HM), low middle (LM), and low (L) levels of development. Punjab (0.47), Haryana (0.51), Gujarat (0.59), and Madhya Pradesh (0.60) emerged as the most agriculturally developed states. Significant factors, namely gross irrigated area, mechanisation and technical adoption (tube wells), productivity [wheat (Triticum aestivum L.), maize (Zea mays L.), and vegetables], input usage (chemical fertiliser), and economic dimension of agriculture [sugarcane (Saccharum officinarum L.) returns] were identified among the development indicators. Enhancing these factors could improve the socio-economic conditions of Indian farmers. The study suggested that the low-developed states require improvements in various dimensions in most indicators to enhance the overall development of agriculture.